SOCIAL AND PSYCHOLOGICAL FACTORS OF DEVIANT BEHAVIOR OF ADOLESCENTS - ASIEIEVA Yuliia; KOVALSKA Natalia (EcoSoEn: Ştiinţe Economice, Sociale şi Inginereşti = Economics, Social and Engineering Sciences)
Analyzing the latest statistical data, it is possible to state an increase in the rates of administrative and criminal violations associated with aggressive behavior (bullying, cyberbullying) among young people; an increase in the number of young people with non-chemical and chemical addictions is also being monitored. All this actualizes the need for scientific and experimental research into the sociopsychological factors that determine deviant behavior among the younger generation, which has practically transferred its life processes to cyberspace. Based on the results of our own psychodiagnostic research, it was found that adolescents from single-parent families tend to focus on the general opinion of the group and need the support and approval of others. This category of adolescents also exhibits a high level of aggressiveness, increased frustration, significant situational anxiety and pessimism towards their own future.